A Study on Set Up Variations During Treatment, and Assessment of Adequacy of Current CTV-PTV Margins in Head and Neck Radiotherapy - Narendran, Arun P; Erakkotan, Greeshma K; Muttath, Geetha; Ajayakumar, Silpa; Anilkumar, Bindu; Suresh, Bindhya (Asian Pacific Journal of Cancer Care, 2022)
Introduction: 3DCRT and IMRT demands high accuracy in patient positioning and accurate and faithful reproducibility of the treatment position right from the day of acquisition of planning scans and throughout the entire duration of radiation treatment delivery. Inadequacies in the accurate reproduction of the treatment positions during each fraction can lead to setup variations which can significantly compromise the ultimate precision of idealized treatment delivery. Materials and methodology: We retrospectively analysed the daily setup variations in patients with head and neck malignancies who received radical or adjuvant radiotherapy from January 2018 to June 2018. A CTV-PTV margin of 0.5 cm is used at our centre. The average displacement from the reference treatment position in lateral, longitudinal and vertical directions were calculated based on CBCT shifts recorded during the entire course of treatment. Results: 101 patients were included in the study (45.54% radical radiotherapy and 54.45% postoperative radiotherapy). The mean shift in any direction was between 0.13 cm and 0.19 cm in the study population as a whole, in radically treated patients and postoperative patients. The shift in any direction of more than 0.5 cm occurred only once or twice during the entire treatment period per patient, except one postoperative patient. The frequency of shift was more in postoperative patients. The mean shifts in the lateral and longitudinal directions were significantly more for postoperative patients (p 0.008 and 0.014 respectively). Conclusions: The CTV to PTV expansion margin used at our institute is adequate for radically treated patients with head and neck cancers both in definitive and postoperative settings. The smaller mean shifts (<2mm) and low frequency of shifts points to the potential for reducing the current CTV to PTV expansion, which needs to be validated in larger studies.